2016
DOI: 10.1002/ana.24789
|View full text |Cite
|
Sign up to set email alerts
|

RNAi prevents and reverses phenotypes induced by mutant human ataxin‐1

Abstract: Objective Spinocerebellar ataxia type 1 is an autosomal dominant fatal neurodegenerative disease caused by a polyglutamine expansion in the coding region of ATXN1. We showed previously that partial suppression of mutant ataxin-1 (ATXN1) expression, using virally-expressed RNAi triggers, could prevent disease symptoms in a transgenic mouse model and a knock in mouse model of the disease, using a single dose of virus. Here, we set out to test if RNAi triggers targeting ATXN1 could not only prevent, but also reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 29 publications
0
49
1
5
Order By: Relevance
“…We used a virus with AAV2/5, which we have used in the past to robustly and reliably express genes in the rodent brain ( 26 , 43 , 47 , 48 ). While there are many serotypes of AAV that can be effective in the brain ( 49 ), AAV2 is currently in clinical trials for PD (NCT# NCT0162158).…”
Section: Discussionmentioning
confidence: 99%
“…We used a virus with AAV2/5, which we have used in the past to robustly and reliably express genes in the rodent brain ( 26 , 43 , 47 , 48 ). While there are many serotypes of AAV that can be effective in the brain ( 49 ), AAV2 is currently in clinical trials for PD (NCT# NCT0162158).…”
Section: Discussionmentioning
confidence: 99%
“…14 They are caused by a CAG trinucleotide repeat expansion, and represent four of the nine known polyglutamine expansion disorders. 16 Importantly, gene silencing strategies have shown efficacy with model systems of SCAs 1719 and intensive efforts are underway to translate these therapeutics to patients.…”
mentioning
confidence: 99%
“…RNAi has been proposed as a strategy for gene therapy of genetic disorders. As a good example of this approach, Keiser et al [17] reported that spinocerebellar ataxia type 1 could be reversed by RNAi therapy. These researchers had previously shown that partial suppression of mutant ataxin-1 gene expression following delivery of a single dose of virus could prevent the development of disease symptoms in a transgenic mouse model and a knock-in mouse model of the disease [18].…”
Section: Rna-targeting Strategiesmentioning
confidence: 99%
“…Their subsequent investigations then showed that RNAi not only prevented, but also reversed disease development when delivered after the onset of symptoms. In this study, a recombinant adeno-associated virus expressing an artificial miRNA targeting human ATXN1 mRNA was delivered at multiple doses in a mouse model of spinocerebellar ataxia type 1, before or after symptom onset [17].…”
Section: Rna-targeting Strategiesmentioning
confidence: 99%